A simple numerical study on sustainable development with genuine saving - Masayuki Sato; Sovannroeun Samreth; Katsunori Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2008)
This paper provides numerical examinations on sustainability of genuine saving (GS) using theWorld Bank database. Unlikely to previous criteria of sustainability, we consider future sustainability by focusing on evolution of GS. In this case even if the historical average GS of a country is positive, there is a possibility that the GS become negative in the future, depending on time series path of the GS. We will show that some countries that were argued to be sustainable in previous studies are shown to be otherwise.
Keywords: Q01; O13; 330; Sustainability; Genuine Saving